Preferred child number as the primary determinant of higher parity in women aged 45-49 in Eastern Indonesia: the 2017 IDHS data analysis - Putri, Nur A'isyah Amalia; Hastono, Sutanto Priyo; Besral (BKM Public Health and Community Medicine, 2023)
Purpose: This research aims to determine the determinants of higher parity in women aged 45-49 years in Eastern Indonesia. Methods: This research uses a quantitative approach and analysis of secondary data from the 2017 IDHS, utilizing a cross-sectional study design. Meanwhile, this research was conducted on 1,055 samples of the 2017 IDHS and analyzed using a complex survey method. Results: The research finds that 72.2% of women aged 45-49 years in Eastern Indonesia have higher parity. Multiple logistic regression analysis indicates that women in this age group who gave birth for the first time before the age of 20 (p-value: 0.005; aOR: 2.04), those who have used a birth control method or device (p-value: 0.001; aOR: 0.30), those with the lowest welfare index (p-value: 0.015; aOR: 1.90), those who have experienced child mortality (p-value: 0.001; aOR: 4.46), and those preferred more than two children (p-value: 0.001; aOR: 5.47) are statistically significant related to higher parity. Conclusion: The research concludes that key determinants of higher parity in women aged 45-49 years in Eastern Indonesia include early age at first birth, previous use of a birth control method or device, lowest welfare index, experience of child mortality, and a preference for having more than two children. Among these, the preferred child number is the most dominant variable related to higher parity.